Menggali Potensi Lokal Kota Melalui Pengembangan UMKM Kampung Semanggi Surabaya - Agizca Aurel Syerinatasya; Dina Septiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Creative industries are industries that rely on the skills, creativity and talents of individuals to generate employment and prosperity. The government has launched the concept of